TAAC: Secure and Efficient Time-Attribute-Based Access Control Scheme in SDN-IoT - Jiamin Hu; Zhonghua Shen; Kefei Chen; Yuying Liu; Qian Meng; Fuqun Wang; Yong Liu (IET Information Security)
The convergence of software-defined networking (SDN) and the Internet of Things (IoT) provides a scalable method for handling the considerable volumes of data produced by IoT devices. However, the lack of appropriate security measures can lead to unauthorized access to sensitive data, potential breaches, and privacy violations, as well as time-consuming and inefficient data retrieval methods in SDN-IoT systems that require decrypting the entire dataset. To address these challenges, this article proposes the time-attribute-based access control scheme in SDN-IoT (TAAC). The TAAC scheme combines ciphertext-policy attribute-based encryption with a novel time-attribute-based access tree to ensure fine-grained access control on time and attributes, enabling secure ciphertext interaction and information sharing across domains. Furthermore, the TAAC scheme also incorporates searchable encryption, which enhances the efficiency of data retrieval. By implementing searchable encryption techniques, the data receiver can generate trapdoors to search and retrieve specific encrypted data without the need to decrypt the entire dataset. In summary, the TAAC scheme improves storage efficiency and computation, enhances scalability, and provides robust security, offering an efficient and secure solution for ciphertext sharing in SDN-IoT environments. Experimental results have demonstrated that the TAAC scheme shows excellent performance and outperforms other attribute-based searchable encryption algorithms.